Strategic Planning and service provision in Greek Local government: a comparative assessment - Plimakis, Sifis (Advances in Social Sciences Research Journal, 2018)
This paper evaluates the impact of strategic planning on the performance of municipal services in Greece in lieu of the recent policy reforms. Improvement in public performance management has been the core tenet in the Greek Local Government Reform, now spanning over two decades. The recent “Kallikratis’’ reform program triggered significant structural re-organization across local government organizations in an attempt to address and resolve centralization and democratic deficit problems, but its impact on municipal services performance remained particularly limited Evidence confirmed marginal improvements in services efficiency and quality, but not substantial enough to inspire municipalities’ economic sustainability and citizens’ level of trust and satisfaction. Performance and governance deficits in municipal services provision, arising from the inherent restrictions of social capital in Greece, characterized by low rates of trust and collaboration, the Weberian characteristics of the hierarchal and centralized decision making in local government, the existence of multiple and overlapping levels and categories of audits and the failure to integrate innovative policy tools for better design and delivery of municipal services). These deficits reflected a lack of an effective national policy for the promotion of strategic management and performance measurement and the limited compliance of local government authorities with their tools and management models. Based on the combination qualitative and quantitative empirical data, this research thus, evaluates and analyzes the existence, perception, and impact of strategic management tools on municipal services performance, by focusing on 39 municipal authorities and 8 service sectors.